An evaluation of business-to-business electronic commerce marketplaces (e-marketplaces) in Malaysia / Nor Azzyati Hashim, Mardziah Hashim and Rogayah Abdul Majid - Hashim, Nor Azzyati; Hashim, Mardziah; Abdul Majid, Rogayah (Institute of Research, Development and Commercialization (IRDC), 2007)
The development of business-to-business electronic commerce marketplaces (B2B e-marketplaces) has influenced the way businesses are conducted. The emergence of many types of e-marketplaces together with the increase use of e-marketplaces allows many organizations to become e-market makers in the electronic commerce environment. Nonetheless, too many B2B e-marketplaces could become a challenge with e-marketplaces have shown numerous successes and failures since early existence. With this background, this pap er discusses the characteristics and success factors of B2B e-marketplaces offered in Malaysia. A content analysis ofe-marketplace websites using the integrated model from the Extended Model of Internet Commerce Adoption (eMICA) and the Internet-Based B2B Stages of Growth enabled an examination of type, ownership, B2B features and B2B stages of growth. A few e-marketplaces were then selected as case studies to identify the success factors based on the Framework of the Critical Success Factors Analysis fo r E-Marketplaces. Overall, Malaysia B2B public e-marketplaces have shown positive growth development stages across time with high adoption of e-commerce website features. In addition,factors of strategic, functional, technology, build liquidity, create value and others were also essential for t e success of the e-marketplaces. Indeed, good marketing strategies, multiple income streams, value added information services and government initiatives are among keys to success.